Documentação museológica: uma reflexão sobre o tratamento descritivo do objeto no Museu Paulista - Yassuda, Silvia Nathaly [UNESP] (2009)
The museum is a unit of information that can provide various types of documentary support, such as the iconography, the three-dimensional and the bibliographic. The museum documentation works with treatment of collections information, from the registration until the dissemination of information, leaving it to operate a system that attends the information demand of its public. In this regard, we point out the need for the use of languages documented in the construction of systems documentary museum, offering to maximize the recovery and use of information. Some peculiarities of the documentation in museums must be met in order to justify the lack of standardization in the record of collections. Within the museum documentation, the research focuses on the cataloging of objects in museums as action mediator between the public and the body, helping in knowledge construction and preservation of memory. Thus, there was a study of the Museu Paulista aiming to subsidize the general documentary procedures and practices of museums with reflections from the Theory of Documentation. As to the specific objectives intended to reflect on the role of documentation in the museum informacional context and observe how the descriptive representation is used in the Museu Paulista.